Extention Transformation Used in I Ching (Global Journal of Science Frontier Research, 2012)
In this paper we show how to using the extension transformation in I Ching in order to transforming a hexagram to another one. Each binary hexagram (and similarly the previous trigram) has a degree of Yang and a degree of Yin. As in neutrosophic logic and set, for each hexagram there is corresponding an opposite hexagram , while in between them all other hexagrams are neutralities denoted by ; a neutrality has a degree of and a degree of . A generalization of the trigram (which has three stacked horizontal lines) and hexagram (which has six stacked horizontal lines) to n-gram (which has n stacked horizontal lines) is provided. Instead of stacked horizontal lines one can consider stacked vertical lineswithout changing the composition of the trigram/hexagram/n-gram. Afterwards, circular representations of the hexagrams and of the n-grams are given.
Keywords: trigram; hexagram; stacked; neutrosophic